Copolymer, preparation method and use thereof, and lithium ion battery
By adding porous copolymers containing methyl functional groups to the PEO-based solid electrolyte, the problem of easy crystallization of PEO-based electrolyte is solved, and the transmission performance of lithium ions and the cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202411575325.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-04-04
AI Technical Summary
PEO-based solid electrolytes are prone to crystallization at room temperature, resulting in a decrease in the transmission performance of lithium ions, weakening the ion conductivity of the electrolyte and the migration ability of lithium ions, which in turn affects the cycling performance of lithium ion batteries.
Porous copolymers containing methyl functional groups are used as additives for solid electrolytes. Through hydrogen bond interactions with the PEO chain segment and the lithium salt, the crystallinity and glass transition temperature of the PEO-based electrolyte are reduced, and the movement of lithium ions is promoted.
The ionic conductivity of PEO-based solid electrolyte is improved, the migration of lithium ions is promoted, the growth of lithium dendrites is inhibited, and the circulation stability of the battery is enhanced.
Smart Images

Figure CN119751783A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a copolymer, a preparation method and use thereof, and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries have attracted much attention in energy storage devices due to their high energy density and high theoretical specific capacity. At present, the application of lithium-ion batteries has spread to various aspects such as household items, military energy, aerospace energy, and vehicle energy. Especially in recent years, the rapid development of the electric vehicle industry has led to a gradual increase in its sales. How to obtain power batteries with longer driving range and greater safety is a challenge facing electric vehicles. Traditional liquid organic electrolytes have low vapor pressure and side reactions with lithium metal that cause thermal failure, making lithium-ion batteries develop slowly in the direction of high energy density. Therefore, in order to solve the safety problems of lithium-ion batteries, it is necessary to replace organic electrolytes with solid electrolytes to solve the above problems.
[0003] Among solid electrolytes, PEO-based solid electrolytes are widely used in polymer solid electrolytes because of their good flexibility and cheap and easy-to-obtain materials. However, PEO-based solid electrolytes are easy to crystallize at room temperature. PEO polymers rely on the movement of amorphous chain segments in the amorphous region to transport lithium ions. After crystallization, the chain segments' lithium ion transport performance decreases, and their ion conductivity and lithium ion migration capacity decrease, resulting in increased interface impedance between the electrolyte and the positive and negative electrodes, uneven lithium ion deposition and the growth of lithium dendrites, which reduces cycle performance. These problems limit the application of solid-state lithium-ion batteries. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a copolymer, a preparation method and use thereof, and a lithium-ion battery.
[0005] In order to achieve the above-mentioned object, according to the first aspect of the present technical solution, the present technical solution provides a copolymer, which comprises a structural unit represented by chemical formula (1):
[0006]
[0007] Among them, R 1 -R 8 Each is independently -H or methyl.
[0008] Furthermore, in the copolymer, R 1 -R 8 All are -H.
[0009] Furthermore, in the copolymer, R 1 , R 2 , R3 , R 4 , R 5 , R 6 and R 8 Both -H, R 7 is methyl; or
[0010] R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 Both -H, R 1 It is methyl.
[0011] Furthermore, in the copolymer, R 1 , R 2 , R 3 , R 4 , R 5 and R 8 Both -H, R 6 and R 7 All are methyl.
[0012] In order to achieve the above-mentioned purpose, according to the second aspect of the present technical solution, the present technical solution also discloses the use of the copolymer provided in the first aspect as an additive for a solid electrolyte.
[0013] In order to achieve the above-mentioned purpose, according to the third aspect of the present technical solution, the present technical solution also discloses a method for preparing the copolymer provided in the first aspect.
[0014] The method for preparing the copolymer comprises: polymerizing the compound monomer represented by chemical formula (2) and melamine monomer to obtain the copolymer.
[0015]
[0016] Among them, R 1 -R 8 Each is independently -H or methyl.
[0017] Furthermore, the molar ratio of the compound monomer represented by the chemical formula (2) to the melamine monomer is 3:4.
[0018] In order to achieve the above-mentioned purpose, according to the fourth aspect of the technical solution, the technical solution also provides a solid electrolyte. The solid electrolyte comprises the following raw material components: lithium salt, polymer matrix and the copolymer provided in the first aspect.
[0019] Furthermore, the copolymer accounts for 1 to 5 wt % of the polymer matrix.
[0020] In order to achieve the above-mentioned purpose, according to the fifth aspect of the technical solution, the technical solution also provides a lithium-ion battery. The lithium-ion battery comprises the solid electrolyte disclosed in the fourth aspect.
[0021] The copolymer provided by the present invention can be used as an additive for a solid electrolyte. By designing a porous polymer containing a methyl functional group, the porous polymer containing a methyl functional group can interact with a PEO segment and a lithium salt through hydrogen bonds, thereby reducing the crystallinity and glass transition temperature of the PEO-based solid electrolyte, increasing the segment movement of the amorphous phase of the PEO segment, accelerating the movement of lithium ions in the PEO-based electrolyte, improving the ionic conductivity of the PEO-based solid electrolyte, promoting the migration of lithium ions, and inhibiting the growth of lithium dendrites, thereby improving the cycle stability of the PEO-based solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the 2-methylanthraquinone-melamine copolymer prepared in Example 3 of the present invention.
[0023] Figure 2 is a Nyquist curve corresponding to the solid electrolyte in Example 6 of the present invention;
[0024] Figure 3 The battery cycle performance diagram corresponding to the solid electrolyte and pure PEO solid electrolyte in Example 6 of the present invention;
[0025] Figure 4 is a Nyquist curve corresponding to the solid electrolyte in Example 8 of the present invention;
[0026] Figure 5 The battery cycle performance diagram corresponding to the solid electrolyte in Example 8 of the present invention and the pure PEO solid electrolyte in Comparative Example 2;
[0027] Figure 6 is a Nyquist curve corresponding to the solid electrolyte in Example 9 of the present invention;
[0028] Figure 7 This is a battery cycle performance diagram corresponding to the solid electrolyte in Example 9 of the present invention and the pure PEO solid electrolyte in Comparative Example 2.
[0029] Figure 8 is the XRD pattern of the solid electrolyte membrane prepared in Examples 8 and 9 of the present invention;
[0030] Fig. 9 is a graph of the glass transition temperature of the solid electrolyte membranes prepared in Examples 8 and 9 of the present invention;
[0031] Fig.10 It is the SEM picture of the product obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The present invention discloses a copolymer and a method for preparing the same. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The products, processes and applications described in the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of this application.
[0033] It should be noted that, in this document, relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a..." does not exclude the presence of other identical elements in the process, method, article or device comprising the element.
[0034] Hereinafter, preferred embodiments of the present invention will be described in detail.
[0035] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0036] An embodiment of the present application provides a copolymer comprising a structural unit represented by chemical formula (1).
[0037]
[0038] Among them, R 1 -R8 Each independently represents -H or methyl. It should be noted that the copolymer contains a plurality of structural units represented by chemical formula (1), that is, the structural unit represented by chemical formula (1) is a repeating unit of the copolymer. The wavy line in chemical formula (1) indicates that the carbon atom on the triazine ring is connected to the nitrogen atom in -NH- of another repeating unit through a chemical bond.
[0039] Optionally, in the structural unit represented by chemical formula (1), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 All are -H, that is, the structural unit represented by chemical formula (1) is chemical formula (1-1).
[0040]
[0041] Optionally, in the structural unit represented by chemical formula (1), R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 Both -H, R 1 is methyl, that is, the structural unit represented by chemical formula (1) is chemical formula (1-2).
[0042]
[0043] Optionally, in the structural unit represented by chemical formula (1), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 and R 8 Both -H, R 7 is a methyl group, that is, the structural unit represented by the chemical formula (1) is the chemical formula (1-3).
[0044]
[0045] Optionally, in the structural unit represented by chemical formula (1), R 1 , R 2 , R 3 , R 4 , R 5 and R 8 Both -H, R 6 and R 7All of them are methyl groups, that is, the structural unit represented by chemical formula (1) is chemical formula (1-4).
[0046]
[0047] Optionally, in the structural unit represented by chemical formula (1), R 2 , R 3 , R 5 , R 6 , R 7 and R 8 Both -H, R 1 and R 4 All of them are methyl groups, that is, the structural unit represented by chemical formula (1) is chemical formula (1-5).
[0048]
[0049] The embodiment of the present invention also discloses a method for preparing a copolymer comprising a structural unit represented by chemical formula (1). Specifically, the method for preparing the copolymer comprises polymerizing a compound monomer represented by chemical formula (2) and a melamine monomer represented by chemical formula (3) to obtain a copolymer comprising a structural unit represented by chemical formula (1).
[0050]
[0051] Among them, R 1 -R 8 Each is independently -H or methyl.
[0052] Wherein, the compound represented by chemical formula (2) is anthraquinone or anthraquinone derivative after methyl substitution at different positions of anthraquinone. The preparation process of the copolymer is carried out in an inert gas atmosphere or a vacuum glove box. The inert gas used can be nitrogen or argon. The anthraquinone or anthraquinone derivative and melamine monomer shown in chemical formula (2) are placed in a pure solvent, and the temperature is increased to the target temperature by a gradient program and maintained for a set time; after the set time, the temperature is lowered to room temperature to obtain a reaction turbid liquid, and the reaction turbid liquid is centrifuged and washed with dimethyl sulfoxide and ethanol, and then dried at 100°C in a vacuum environment to obtain a porous copolymer powder. The target temperature is preferably 170°C, the set time is preferably more than 72 hours, and the solvent in the polymerization process can be selected from at least one of dimethyl sulfoxide and N,N-dimethylformamide.
[0053] Preferably, the molar ratio of the compound monomer represented by chemical formula (2) to the melamine monomer is 3:4, so that the anthraquinone or its derivative monomer can fully react with the melamine monomer to obtain a copolymer with a three-dimensional spatial structure.
[0054] Preferably, during the polymerization reaction, the temperature is controlled by a programmed temperature increase method from 50°C to the target temperature. When the target temperature is 170°C, the temperature is increased by 10°C every 2 hours between 50°C and 130°C, the temperature is increased by 10°C every 6 hours between 130°C and 150°C, and the temperature is increased by 10°C every 12 hours between 150°C and 170°C.
[0055] The present invention also correspondingly protects the use of a copolymer having a structural unit represented by the chemical formula (1) as an additive for a solid electrolyte. The researchers found that when a copolymer having a structural unit represented by the chemical formula (1) is used as an additive to prepare a PEO-based solid electrolyte, the copolymer composed of the structural unit represented by the chemical formula (1) is a porous polymer structure containing methyl functional groups. The addition of the porous polymer generated by copolymerization can interact with the PEO chain segments and the lithium salt through hydrogen bonds such as NH, HO, and HF, thereby reducing the crystallinity of the PEO-based solid electrolyte, accelerating the movement of lithium ions in the PEO-based electrolyte, improving the ionic conductivity of the PEO-based solid electrolyte, promoting the migration of lithium ions, and inhibiting the growth of lithium dendrites, thereby improving the cycle stability of the PEO-based solid electrolyte.
[0056] The embodiment of the present invention also provides a specific composition of the solid electrolyte, which includes the following raw material components: lithium salt, polymer matrix and copolymer having a structural unit represented by chemical formula (1), wherein the percentage of the copolymer to the polymer matrix mass is preferably 1-5wt%, more preferably 2-4wt%.
[0057] The preparation method of the solid electrolyte comprises: fully mixing a lithium salt, a solvent and a polymer matrix to obtain an electrolyte slurry; mixing a copolymer having a structural unit represented by chemical formula (1) with the electrolyte slurry to obtain an electrolyte mixture; pouring the electrolyte mixture into a mold by a solution casting method and vacuum drying to obtain a solid electrolyte.
[0058] The material of the polymer matrix is at least one of PEO, PAN, PEG, PVDF, and PVDF-HFP; the lithium salt is at least one of LiTFSI, LiFSI, LiFTFSI, LiPF6, LiClO4, LiBOB, and LiBF4. Preferably, the molar ratio of lithium in the conductive lithium salt to the repeating unit in the polymer matrix is 1:(10-20). The solvent used in the preparation method of the solid electrolyte is a solvent that can dissolve the polymer matrix, preferably at least one of acetonitrile, toluene, acetone, and cyclohexane.
[0059] The embodiments of the present invention also protect a lithium-ion battery, which uses the solid electrolyte of the aforementioned embodiments of the present application. The specific preparation process of the lithium-ion battery can refer to the prior art and will not be repeated here. The specific types of lithium-ion batteries include but are not limited to lithium iron phosphate batteries.
[0060] Example 1: Preparation of anthraquinone-melamine copolymer.
[0061]
[0062] The structural formula of the raw material anthraquinone is chemical formula (2-1), and the structural formula of melamine is chemical formula (3). The two are mixed at a ratio of 3:4. Specifically, anthraquinone (0.12 mol / L) and melamine (0.16 mol / L) are mixed in DMSO, and the temperature is controlled by gradient heating from 50°C to 170°C, 10°C every 2 hours between 50°C and 130°C, 10°C every 6 hours between 130°C and 150°C, and 10°C every 12 hours between 150°C and 170°C. The reaction obtains a turbid liquid, which is centrifugally washed with dimethyl sulfoxide and ethanol, and then dried at 100°C under vacuum to obtain an anthraquinone-melamine copolymer powder, which contains the repeating unit shown in chemical formula (1-1). After testing the SEM image of the obtained product, it can be seen that the product prepared in this embodiment has a porous structure.
[0063] Example 2: Preparation of 1-methylanthraquinone-melamine copolymer.
[0064]
[0065] The structural formula of the raw material 1-methylanthraquinone is chemical formula (2-2), and the structural formula of melamine is chemical formula (3). The two are mixed at a ratio of 3:4. Specifically, 1-methylanthraquinone (0.12 mol / L) and melamine (0.16 mol / L) are mixed in DMSO, and the temperature is controlled by gradient heating from 50°C to 170°C, 10°C every 2 hours between 50°C and 130°C, 10°C every 6 hours between 130°C and 150°C, and 10°C every 12 hours between 150°C and 170°C. The reaction obtains a turbid liquid, which is centrifugally washed with dimethyl sulfoxide and ethanol, and then dried at 100°C under vacuum to obtain a 1-methylanthraquinone-melamine copolymer powder, which contains the repeating unit shown in chemical formula (1-2). After testing the SEM image of the obtained product, it can be seen that the product obtained in this embodiment has a porous structure.
[0066] Example 3: Preparation of 2-methylanthraquinone-melamine copolymer.
[0067]
[0068] The structural formula of the raw material 2-methylanthraquinone is chemical formula (2-3), and the structural formula of melamine is chemical formula (3). The two are mixed at a molar ratio of 3:4. Specifically, 2-methylanthraquinone (0.12 mol / L) and melamine (0.16 mol / L) are mixed in DMSO, and the temperature is controlled by a gradient heating method, from 50°C to 170°C, and the temperature is increased by 10°C every 2 hours between 50°C and 130°C, and the temperature is increased by 10°C every 6 hours between 130°C and 150°C, and the temperature is increased by 10°C every 12 hours between 150°C and 170°C. A turbid liquid is obtained by reaction, and the turbid liquid is centrifugally washed with dimethyl sulfoxide and ethanol, and then dried at 100°C under vacuum conditions to obtain a 2-methylanthraquinone-melamine copolymer powder, which contains repeating units shown in chemical formula (1-3), and its SEM image is as shown Figure 1 As shown, it can be seen that the 2-methylanthraquinone-melamine copolymer prepared in this example presents a porous structure.
[0069] Example 4: Preparation of 2,3-dimethylanthraquinone-melamine copolymer.
[0070]
[0071] The raw material 2,3-dimethylanthraquinone has a structural formula of chemical formula (2-4), and the structural formula of melamine has a structural formula (3). The two are mixed at a molar ratio of 3:4. Specifically, 2,3-dimethylanthraquinone (0.12 mol / L) and melamine (0.16 mol / L) are mixed in DMSO, and the temperature is controlled by a gradient heating method, from 50°C to 170°C, 10°C every 2 hours between 50°C and 130°C, 10°C every 6 hours between 130°C and 150°C, and 10°C every 12 hours between 150°C and 170°C, to obtain a turbid liquid, which is centrifugally washed with dimethyl sulfoxide and ethanol, and then dried at 100°C under vacuum to obtain a 2,3-dimethylanthraquinone-melamine copolymer powder, which contains the repeating unit shown in chemical formula (1-4). After testing the SEM image of the obtained product, it can be seen that the product obtained in this embodiment has a porous structure.
[0072] Example 5: Preparation of 1,4-dimethylanthraquinone-melamine copolymer.
[0073]
[0074] The raw material 1,4-dimethylanthraquinone has a structural formula of chemical formula (2-5), and the structural formula of melamine has a structural formula of chemical formula (3). The two are mixed at a ratio of 3:4. Specifically, 1,4-dimethylanthraquinone (0.12 mol / L) and melamine (0.16 mol / L) are mixed in DMSO, and the temperature is controlled by a gradient heating method, from 50°C to 170°C, 10°C every 2 hours between 50°C and 130°C, 10°C every 6 hours between 130°C and 150°C, and 10°C every 12 hours between 150°C and 170°C, to obtain a turbid liquid, which is centrifugally washed with dimethyl sulfoxide and ethanol, and then dried at 100°C under vacuum to obtain a 1,4-dimethylanthraquinone-melamine copolymer powder, which contains the repeating unit shown in chemical formula (1-5). After testing the SEM image of the obtained product, it can be seen that the product obtained in this embodiment has a porous structure.
[0075] Comparative Example 1
[0076] The structural formula of the raw material 2-ethylanthraquinone is chemical formula (2-6), and the structural formula of melamine is chemical formula (3). The two are mixed at a molar ratio of 3:4. Specifically, 2-ethylanthraquinone (0.12 mol / L) and melamine (0.16 mol / L) are mixed in DMSO, and the temperature is controlled by a gradient heating method, from 50°C to 170°C, and the temperature is increased by 10°C every 2 hours between 50°C and 130°C, and the temperature is increased by 10°C every 6 hours between 130°C and 150°C, and the temperature is increased by 10°C every 12 hours between 150°C and 170°C. The reaction obtains a turbid liquid, and the turbid liquid is centrifugally washed with dimethyl sulfoxide and ethanol, and then dried at 100°C under vacuum conditions to obtain a 2-ethylanthraquinone-melamine copolymer powder. The SEM image of the obtained product is as follows: Fig.10 As shown, it can be seen that the product prepared in this embodiment has almost no porous structure, and a large amount of melamine monomer can still be detected in the product after the reaction. The researchers analyzed that the reason is that since the ethyl substituent on the anthraquinone ring is longer than the carbon chain of the methyl group, the copolymer unit of the structure shown in the chemical formula (1) is an extended structure in space, and the presence of the ethyl group has a larger steric hindrance effect than the methyl group in the formation of the copolymer stereostructure, resulting in poor subsequent synthesis reaction effect, 2-ethylanthraquinone and melamine cannot be completely reacted in a ratio of 3:4, a large number of melamine units cannot be connected to the anthraquinone structure, and a complete three-dimensional spatial structure cannot be formed, resulting in the product The porosity cannot meet the requirements.
[0077]
[0078] Example 6
[0079] The anthraquinone-melamine copolymer prepared in Example 1 was added to an electrolyte slurry of PEO, lithium salt and acetonitrile solvent at a rate of 3% of the total added mass of PEO, and was prepared by a solution casting method. After the solvent was dried at 80°C for 24 hours, a solid electrolyte membrane containing a porous polymer was obtained. The thickness of the solid electrolyte membrane was 170μm-220μm.
[0080] The battery was assembled in a glove box with a water and oxygen content of less than 0.01ppm. The battery was assembled in the order of positive electrode shell, positive electrode sheet, solid electrolyte membrane, metal lithium negative electrode, gasket, shrapnel, and negative electrode shell. After the battery was assembled, plastic tweezers were used to clamp the battery and place it on the seal for pressing. After the pressing was completed, the battery was placed in the hatch of the box and taken out for electrochemical performance testing. The assembled button battery had a positive electrode of lithium iron phosphate and a negative electrode of metal lithium. The loading amount of lithium iron phosphate was 1.5-2.2mg / cm 2 .
[0081] The positive and negative electrodes of the battery are connected to an electrochemical workstation, the AC impedance of the battery is measured, and the Nyquist plot of the solid electrolyte is obtained. Figure 2 As shown, the coordinate axis corresponds to a complex plane, the abscissa on the complex plane represents the real part, corresponding to the resistance of the solid electrolyte, and the ordinate represents the imaginary part, corresponding to the reactance of the solid electrolyte. Figure 2 In the figure, the AC impedance consists of a semicircle and a straight line with an inclination of about 45°, where the diameter of the semicircle represents the resistance value of the solid electrolyte, which is 38Ω.
[0082] The lithium ion conductivity was calculated by the following formula.
[0083]
[0084] Where σ represents the ionic conductivity, S represents the working electrode area of the battery (referring to the area of the positive electrode of the battery or the area of the negative electrode of the battery). The diameter of the button cell used in this embodiment is 16 mm, and the calculated working electrode area is 2.0 cm 2 , l represents the thickness of the solid polymer electrolyte membrane, R b It represents the resistance value of the electrolyte.
[0085] The above formula shows that: Under the test environment, when the temperature outside the battery is 60°C, Figure 2 The lithium ion conductivity shown is 2.88*10 -4 S / cm.
[0086] Figure 3 This is the battery cycle performance diagram of Example 6 of the present invention. Under the test conditions of 60°C and 1C, the initial capacity is 142 mAh g -1After 200 cycles, the battery capacity is 97.3Ah g -1 , the capacity retention rate is 68.5% and the Coulombic efficiency is maintained at nearly 100%.
[0087] Comparative Example 2
[0088] The solid electrolyte membrane was prepared by using pure PEO as the solid electrolyte. The battery was assembled and tested in the same manner as in Example 6. The lithium ion conductivity was 5.47*10-5S / cm. The pure PEO solid electrolyte was tested at 60°C and 1C. Figure 2 The initial capacity shown is 102.9 mAh g -1 After 56 cycles, the battery capacity is 43.98 mAh g -1 , the capacity retention rate was 76%, and the Coulombic efficiency dropped from 99.7% to 43.98%.
[0089] Example 7
[0090] The 1-methylanthraquinone-melamine copolymer obtained in Example 2 was added to the electrolyte slurry at 3% of the total added mass of PEO to prepare a solid electrolyte membrane.
[0091] The battery was assembled and tested in the same manner as in Example 6. The resistance of the solid electrolyte was 28Ω, and the lithium ion conductivity was 5.95*10 -4 S / cm, at 60℃, 1C test conditions, the initial capacity is 146mAh g -1 After 200 cycles, the battery capacity is 131.0 mAh g -1 , the capacity retention rate was 89.7% and the Coulombic efficiency was maintained at nearly 100%.
[0092] Example 8
[0093] The 2-methylanthraquinone-melamine copolymer obtained in Example 3 was added to the electrolyte slurry at a rate of 3% of the total added mass of PEO to obtain a solid electrolyte membrane. The battery was assembled and tested in the same manner as in Example 6 to obtain the Nyquist diagram of the electrolyte and the battery cycle performance diagram as shown in FIG. Figure 4 and Figure 5 The resistance of the solid electrolyte is 30Ω, and the lithium ion conductivity is 6.5*10 -4 S / cm. Under the test conditions of 60℃ and 1C, the initial capacity is 148mAh g -1 After 200 cycles, the battery capacity is 133.2 mAh g -1 , the capacity retention rate is 90% and the Coulombic efficiency is maintained at nearly 100%.
[0094] Example 9
[0095] The 2,3-dimethylanthraquinone-melamine copolymer obtained in Example 4 was added to the electrolyte slurry at 3% of the total added mass of PEO to obtain a solid electrolyte membrane. The solid electrolyte membrane was assembled and tested in the same manner as in Example 6 to obtain the Nyquist diagram of the electrolyte and the battery cycle performance diagram as shown in FIG. Figure 6 and Figure 7 The resistance of the solid electrolyte is 35Ω, and the lithium ion conductivity is 3.45*10 -4 S / cm, at 60℃, 1C test conditions, the initial capacity is 139.5mAh g -1 After 200 cycles, the battery capacity is 123.5 mAh g -1 , the capacity retention rate was 88.1% and the coulombic efficiency was maintained at nearly 100%.
[0096] Example 10
[0097] The 1,4-dimethylanthraquinone-melamine copolymer obtained in Example 5 was added to the electrolyte slurry at a rate of 3% of the total added mass of PEO to obtain a solid electrolyte membrane. The solid electrolyte membrane was assembled and tested in the same manner as in Example 6. The resistance value of the solid electrolyte was 39Ω, and the lithium ion conductivity was 3.0*10 -4 S / cm, at 60℃, 1C test conditions, the initial capacity is 130.5mAh g -1 After 200 cycles, the battery capacity is 112.5 mAh g -1 , the capacity retention rate was 86.2% and the Coulombic efficiency was maintained at nearly 100%.
[0098] Table 1
[0099]
[0100] The index test data of Examples 6-10 and Comparative Example 2 are summarized in Table 1. By comparing Examples 6-10 and Comparative Example 2 in Table 1, it is found that:
[0101] 1. The copolymer obtained by the embodiment of the present invention is used as a solid electrolyte additive. The ionic conductivity and coulombic efficiency are significantly improved compared with those of comparative example 2. Except that the capacity retention rate of example 6 is slightly decreased, the capacity retention rates of examples 7-10 are also significantly improved.
[0102] 2. In the case of the presence of methyl substituents in the copolymers obtained by the embodiments of the present invention, as the number of methyl substituents in the structural compound represented by the raw material chemical formula (2) increases, the effect of the obtained copolymers as solid electrolyte additives is greatly improved compared with the copolymers without methyl substituents. For example, the ion conductivity and capacity retention rate of Examples 7-10 are significantly better than those of Example 6.
[0103] 3. As the number of methyl substituents in the copolymers obtained in the embodiments of the present invention increases, the effect of the copolymers used as solid electrolyte additives shows a trend of first increasing and then decreasing. For example, the effects of Embodiments 7 and 8 having one methyl substituent are better than those of Embodiment 6 having no methyl substituent, while the effects of Embodiments 9 and 10 having two methyl substituents are both worse than those of Embodiments 7 and 8.
[0104] The reason is that the more substituents there are, the stronger the interaction between them and the active sites of the COC bonds on the PEO groups, and the more NH, HO, and HF hydrogen bonds they form with PEO and lithium salts. Only an appropriate amount of methyl-containing porous polymer fillers can construct a continuous Li + The large amount of methyl-containing porous polymer additives will reduce the free volume of PEO segment movement through hydrogen bond interaction, hindering the movement of PEO segment, which is not conducive to Li + migration.
[0105] XRD diffraction experiments were performed on the solid electrolyte membranes prepared in Examples 8 and 9 and the solid electrolyte membrane of pure PEO, respectively, and the following results were obtained: Figure 8 From the XRD diagram of the solid electrolyte shown, it can be seen that the addition of 2-methylanthraquinone-melamine copolymer significantly reduces the crystallinity peak of the solid electrolyte compared to the addition of 2,3-dimethylanthraquinone copolymer additive. It can be seen that the 2-methylanthraquinone copolymer additive in Example 8 has a better effect than the copolymer additive of pure anthraquinone and 2,3-dimethylanthraquinone.
[0106] At the same time, Fig. 9 The solid electrolyte glass transition temperature diagram shown can prove that the 2-methylanthraquinone copolymer additive reduces the glass transition temperature of the PEO composite solid electrolyte membrane from -40.6°C to -41.6°C, indicating that the segmental motion of the amorphous phase of the PEO segment increases. The results further confirm that the addition of 2-methylanthraquinone-melamine copolymer destroys the crystallization of the -EO segment and promotes the motion of the PEO chain, resulting in a decrease in crystallinity and glass transition temperature, thereby enabling better transmission of lithium ions in the electrolyte, providing more free volume and transmission paths for the transmission of lithium ions, improving the ionic conductivity of the PEO-based solid electrolyte, promoting the migration of lithium ions, and improving the cycle stability of the PEO-based solid electrolyte.
[0107] Some embodiments in this specification are described in a progressive manner. Each embodiment focuses on the differences from other embodiments, and the same or similar parts between the embodiments can be referenced to each other.
[0108] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A copolymer comprising a structural unit represented by chemical formula (1), in, R 1 -R 8 Each is independently -H or methyl.
2. The copolymer according to claim 1, characterized in that R 1 -R 8 All are -H.
3. The copolymer according to claim 1, characterized in that R 1 , R 2 , R 3 , R 4 , R 5 , R 6 and R 8 Both -H, R 7 is methyl; or R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 Both -H, R 1 It is methyl.
4. The copolymer according to claim 1, characterized in that R 1 , R 2 , R 3 , R 4 , R 5 and R 8 Both -H, R 6 and R 7 All are methyl.
5. Use of the copolymer according to any one of claims 1 to 4 as an additive for solid electrolytes.
6. The method for preparing a copolymer according to any one of claims 1 to 4, characterized in that: The copolymer is obtained by polymerizing the compound monomer represented by the chemical formula (2) and the melamine monomer. Among them, R 1 -R 8 Each is independently -H or methyl.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the compound monomer represented by the chemical formula (2) to the melamine monomer was 3:
4.
8. A solid electrolyte, characterized in that The invention comprises the following raw material components: a lithium salt, a polymer matrix and the copolymer as claimed in any one of claims 1 to 4.
9. The solid electrolyte according to claim 8, characterized in that The copolymer accounts for 1 to 5 wt % of the polymer matrix.
10. A lithium ion battery, characterized in that: Comprising the solid electrolyte as claimed in claim 8 or 9.
Citation Information
Cited By
Polyethylene oxide-based block copolymer containing carborane hard segment, preparation method and solid electrolyte membrane
CN121405954A